Uncovering the active constituents and mechanisms of Rujin Jiedu powder for ameliorating LPS-induced acute lung injury using network pharmacology and experimental investigations - Ma, Yuhui; Xu, Hong; Chen, Gang; Liu, Wei; Ma, Chao; Meng, Jialei; Yuan, Lin; Hua, Xu; Ge, Guangbo; Lei, Ming (Frontiers in Pharmacology, 2023)
Background: Acute lung injury (ALI) is a common clinical disease with high mortality. Rujin Jiedu powder (RJJD) has been clinically utilized for the treatment of ALI in China, but the active constituents in RJJD and its protective mechanisms against ALI are still unclear. Methodology: ALI mice were established by intraperitoneal injection of LPS to test the effectiveness of RJJD in treating ALI. Histopathologic analysis was used to assess the extent of lung injury. An MPO (myeloperoxidase) activity assay was used to evaluate neutrophil infiltration. Network pharmacology was used to explore the potential targets of RJJD against ALI. Immunohistochemistry and TUNEL staining were performed to detect apoptotic cells in lung tissues. RAW264.7 and BEAS-2B cells were used to explore the protective mechanisms of RJJD and its components on ALI in vitro. The inflammatory factors (TNF-α, IL-6, IL-1β and IL-18) in serum, BALF and cell supernatant were assayed using ELISA. Western blotting was performed to detect apoptosis-related markers in lung tissues and BEAS-2B cells. Results: RJJD ameliorated pathological injury and neutrophil infiltration in the lungs of ALI mice and decreased the levels of inflammatory factors in serum and BALF. Network pharmacology investigations suggested that RJJD treated ALI via regulating apoptotic signaling pathways, with AKT1 and CASP3 as crucial targets and PI3K-AKT signaling as the main pathway. Meanwhile, baicalein, daidzein, quercetin and luteolin were identified as key constituents in RJJD targeting on the above crucial targets. Experimental investigations showed that RJJD significantly upregulated the expression of p-PI3K, p-Akt and Bcl-2, downregulated the expression of Bax, caspase-3 and caspase-9 in ALI mice, and attenuated lung tissue apoptosis. Four active constituents in RJJD (baicalein, daidzein, quercetin and luteolin) inhibited the secretion of TNF-α and IL-6 in LPS-induced RAW264.7 cells. Among these components, daidzein and luteolin activated the PI3K-AKT pathway and downregulated the expression of apoptosis-related markers induced by LPS in BEAS-2B cells. Conclusion: RJJD alleviates the inflammatory storm and prevents apoptosis in the lungs of ALI mice. The mechanism of RJJD in treating ALI is related to the activation of PI3K-AKT signaling pathway. This study provides a scientific basis for the clinical application of RJJD.